Perception of body image in adolescents and the relationship with their nutritional (Research, Society and Development, 2021)
The body image is created from the individual assimilation that each person in his uniqueness creates from himself. In adolescence, an increase in perceptions and reflections on the shape of the body is identified, which may be associated with the standards of beauty imposed by society. Such factors may favor the increase in obesity and eating disorders at this stage of life. The present study aims to assess the self-perception of body image and the nutritional status of high school teenagers from a public school in Fortaleza-CE. This is a cross-sectional study, with a quantitative approach, which evaluated 104 adolescents of both genders. For the assessment of nutritional status, weight and height were measured to calculate the Body Mass Index (BMI), which was converted into a Z-score of BMI / age. For the analysis of the perception of body image, the Body Silhouette Scale (EFS) was used. It was found that in both sexes, a higher frequency of eutrophy was found, 75.95% in females and 60% in males. In relation to body satisfaction and dissatisfaction, 31.48% of women were dissatisfied with their bodies. Among males, 10% were dissatisfied. The results found showed a representative percentage of dissatisfaction in both sexes. It is concluded that the high frequency of body dissatisfaction observed in the present study highlights the need to develop public policies, with a focus on this issue.